Евалуација на ефикасноста на хипербарната оксигено терапија врз заздравувањето на хроничните рани и врз хроничната инфламација - Брешковска, Христина (Медицински факултет, УКИМ, Скопје, 2020)
Introduction: Chronic wounds are defined as wounds in which the order and amount of time of the reparative processes are disrupted. Therefore, it is impossible to establish anatomical and functional integrity, i.e. the reparative processes did not lead to a satisfactory anatomical and functional result. Chronic wounds according to the Wound Healing Society can be divided into 4 major groups: arterial, venous, diabetic, and decubitus. They are also called quiet epidemics and it is estimated that in developed countries 1 – 2 % of the population will have a chronic wound over their lifetime. Chronic wounds have a significant impact on the health and quality of life of patients and their families. They cause pain, disability, depression, financial costs, hospitalization and death. Their treatment requires a complex approach and an interdisciplinary team. Wound healing is a complex and dynamic process of replacing devitalized tissue and missing structures. Many of these processes require additional cellular metabolism for protein synthesis and transport, which requires oxygen therapy under increased pressure (HBOT, hyperbaric oxygen therapy). The main function of HBOT is to supply the injured tissue with enough oxygen by diffusion to meet the metabolic processes of the cells in the wound itself and its surroundings, especially when the vascular supply is compromised. Objectives: The main objective of this study is to demonstrate the effect of hyperbaric oxygen therapy in the healing of chronic wounds and the effect of HBOT on inflammation by determining the proinflammatory cytokines. To evaluate the effectiveness of HBOT in chronic wounds in relation to wound changes (reduction in size or complete epithelialization) compared with the control group. To confirm the effect of HBOT on oxygen saturation before, during and after completing the treatment in the examined groups. Material and method: The study is prospective, randomized and includes 105 patients over 18 years of age, of both sexes with chronic wounds. Of these, 35 patients were a control group, and the rest were divided into 2 groups of 35 patients according to the HBOT protocol that was applied (2.0 ATA and 2.2 ATA protocol). The respondents included in the study were from among the patients who were treated in an outpatient and hospital setting at the University Clinic for Plastic and Reconstructive Surgery in Skopje, Medical faculty, "University Ss. Cyril and Methodius" – Skopje. All respondents were monitored over a 6-month period, with regular controls and standard therapy including dressings and debridement of wounds. The concentrations of serum cytokines, IL - 1, IL - 6, and TNF - α were determined by Luminex technology, which allows multiple cytokines of the same sample to be analyzed simultaneously. Oxygen saturation in the immediate vicinity of the wound was determined by Invos 5100 C Cerebral / Somatic Oximeter – NIRS (Near-infrared spectroscopy), before starting HBOT, at the 20th exposure, immediately after the exposure, and at the end of therapy (immediately after the 40th exposure). The results were statistically processed with SPSS. Results: After analyzing the obtained results, the effectiveness of HBOT as adjuvant therapy in the treatment of chronic wounds was confirmed. The effect of standard therapy together with HBOT as adjuvant treatment is superior in wound healing compared to standard therapy treatment. The reduction in wound surface in patients treated with HBOT was superior compared to the control group. The anti-inflammatory properties of HBOT play an important role in reducing tissue damage and spreading infection. Significant decrease of O2 saturation in the tissuewas confirmed in the wound healing process. Conclusion: Hyperbaric oxygen therapy facilitates healing of chronic wounds and reduces the inflammatory response.
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Лидија Тодоровска.
Keywords: Hyperbaric oxygen therapy (HBOT), chronic wound, inflammation, proinflammatory cytokines, O2 saturation